Function and Role of Regulatory T Cells in Rheumatoid Arthritis - Jiang, Qi; Yang, Guocan; Liu, Qi; Wang, Shengjun; Cui, Dawei (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is a systemic and heterogeneous autoimmune disease with symmetrical polyarthritis as its critical clinical manifestation. The basic cause of autoimmune diseases is the loss of tolerance to self or harmless antigens. The loss or functional deficiency of key immune cells, regulatory T（Treg）cells, has been confirmed in human autoimmune diseases. The pathogenesis of RA is complex, and the dysfunction of Tregs is one of the proposed mechanisms underlying the breakdown of self-tolerance leading to the progression of RA. Treg cells are a vital component of peripheral immune tolerance, and the transcription factor Foxp3 plays a major immunosuppressive role. Clinical treatment for RA mainly utilizes drugs to alleviate the progression of disease and relieve disease activity, and the ideal treatment strategy should be to re-induce self-tolerance before obvious tissue injury. Treg cells are one of the ideal options. This review will introduce the classification, mechanism of action, and characteristics of Treg cells in RA, which provides insights into clinical RA treatment.